KEPEMIMPINAN DIGITAL 4.0: KAJIAN SISTEMATIS KONSEPTUALISASI DAN PRAKTIK DALAM PENDIDIKAN - Abdul Hasan Saragih; Abdul Hamid K; Sugiharto Sugiharto; Awal Kurnia Putra Nasution; Ricki Ananda; Oktaviana Bangun; Iqbal Kamil Siregar; Bachtiar Efendi; Rafika Sari Br Sembiring (STKIP Pesisir Selatan, 2025)
This study presents a comprehensive analysis of the evolution of digital leadership in education, tracing its development from the initial concept of e-leadership to Leadership 4.0 amid the era of digital transformation and artificial intelligence (AI).